Gleeful days with SK Wira & Mahkota - Tuan Sidek, T. M. (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
24 & 27 May 2010. CMLHS Community Services on 24 May turned gleeful with vigorous and candid acts by a group of 176 pupils accompanied by 12 teachers from Sekolah Kebangsaan Wira; and later, on 27 May, 80 pupils with 12 teachers from Sekolah Kebangsaan Seri Mahkota. One day after another, the groups who were UPSR 2010 candidates merrily flocked to UMP looking naive, yet with eager minds mainly to participate in the motivational programmes hosted by the centre.